Conodonts: A Thing of the Past-and of the Future - Barnes, Christopher; Nowlan, Godfrey (Geoscience Canada, 1975)
Summary In the last decade, accelerated studies of those exquisite microfossils, conodonts. have led to new advances in their taxonomy, ultrastructure, biostratigraphy, and paleoecology. There is now a clearer understanding of the arrangement of elements in the apparatus of the conodontophorid animal. Evidence also exists that the animal was largely nektobenthic rather than pelagic in habit. However, the beast is as mysterious as ever, reluctant to divulge its true affinity to a waiting world.